Vulnérabilité, risques et conflits liés à l’eau : la zone de protection environnementale de la plaine inondable du Tietê - Neli Aparecida de Mello-Théry; Hervé Théry; Danilo Pereira Sato; Heloisa de Camargo Tozato (IdeAs)
The article analyses the situation of the Tietê River floodplain Environmental Protection Area (APA-VRT) and the Permanent Preservation Areas (APP) in the context of the metropolitan region of São Paulo, highlighting the vulnerabilities and risks, changes in land use, followed by appreciation of the stakeholders, their actions in the transformation process and their relations with public actions aimed at environmental conservation and the defense of the common good. The text contains 20 illustrations developed by mapping data collected from various statistical sources, image analysis and field work carried out in the APA-VRT.